Assembly and trafficking of box C/D and H/ACA snoRNPs. Issue 6 (3rd June 2017) - Massenet, Séverine; Bertrand, Edouard; Verheggen, Céline
ABSTRACT: Box C/D and box H/ACA snoRNAs are abundant non-coding RNAs that localize in the nucleolus and mostly function as guides for nucleotide modifications. While a large pool of snoRNAs modifies rRNAs, an increasing number of snoRNAs could also potentially target mRNAs. ScaRNAs belong to a family of specific RNAs that localize in Cajal bodies and that are structurally similar to snoRNAs. Most scaRNAs are involved in snRNA modification, while telomerase RNA, which contains H/ACA motifs, functions in telomeric DNA synthesis. In this review, we describe how box C/D and H/ACA snoRNAs are processed and assembled with core proteins to form functional RNP particles. Their biogenesis involve several transport factors that first direct pre-snoRNPs to Cajal bodies, where some processing steps are believed to take place, and then to nucleoli. Assembly of core proteins involves the HSP90/R2TP chaperone-cochaperone system for both box C/D and H/ACA RNAs, but also several factors specific for each family. These assembly factors chaperone unassembled core proteins, regulate the formation and disassembly of pre-snoRNP intermediates, and control the activity of immature particles. The AAA+ ATPase RUVBL1 and RUVBL2 belong to the R2TP co-chaperones and play essential roles in snoRNP biogenesis, as well as in the formation of other macro-molecular complexes. Despite intensive research, their mechanisms of action are still incompletely understood.